2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2795.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential levels of soluble angiopoietin‐2 and Tie‐2 in patients with haematological malignancies

Abstract: The system involving angiopoietin-2 (Ang-2) and its receptor, Tie-2, appears to play an important role not only in tumor angiogenesis, but also in the biology of haematological and non-haematological malignancies. In the present study we evaluated the serum levels of soluble Ang-2 (sAng-2) and soluble Tie-2 (sTie-2) in patients with haematological malignancies. Measurements were carried out in 15 patients with chronic myeloid leukaemia (CML), 25 with essential thrombocythemia (ET), 24 with multiple myeloma (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
4
23
0
1
Order By: Relevance
“…Furthermore, it is conceivable that Ang-2 could also be released by the endothelium of the normal vasculature upon dysregulated stimulation by leukemic blasts [19]. Our findings are in line with a recent observation of elevated Ang-2 and Tie-2 levels in patients with chronic myeloid leukemia (CML) and multiple myeloma [14]. It was found that blood levels of sAng-2 and sTie-2 were strongly associated with the extent of BM infiltration, TLC and LDH, providing indirect evidence that the leukemic blasts themselves at least significantly contributed to the plasma levels of the tested angiogenic factors [19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, it is conceivable that Ang-2 could also be released by the endothelium of the normal vasculature upon dysregulated stimulation by leukemic blasts [19]. Our findings are in line with a recent observation of elevated Ang-2 and Tie-2 levels in patients with chronic myeloid leukemia (CML) and multiple myeloma [14]. It was found that blood levels of sAng-2 and sTie-2 were strongly associated with the extent of BM infiltration, TLC and LDH, providing indirect evidence that the leukemic blasts themselves at least significantly contributed to the plasma levels of the tested angiogenic factors [19].…”
Section: Discussionsupporting
confidence: 91%
“…The overall survival is significantly shorter in AML patients with plasma Ang-2 2500 pg/ml than in those with levels <2500 pg/ml T E22 <=8 >8 <=8-censored >8-censored documented that the tumor cells themselves emit proteins that stimulate neoangiogenesis and this process is correlated with the diffusion of metastases [22]. Elevated levels of circulating Ang-2 have been linked with angiogenesis in malignancies such as angiosarcoma [23], breast cancer [24], and multiple myeloma and CML [14] . In analogy, high levels of Ang-2 in AML may contribute to angiogenesis in the BM in the presence of mitogenic mediators, thereby facilitating leukemic blast proliferation and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, no data are so far available on blood levels of angiopoietins and their soluble receptor Tie2 (sTie2) in AML. Furthermore, while elevated blood levels of Ang-2 have been detected in patients with angiosarcoma, 26 breast cancer, 27 multiple myeloma and chronic myeloid leukemia, 28 to the best of our knowledge, there are no studies available on the prognostic value of soluble angiopoietins in any type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal serum levels of angiopoietin-2 (Ang-2) were found in several hematological malignancies. 3,4 The report of Hü ttmann et al, 5 recently published in Leukemia, described an increase of Ang-2 plasma levels in the ZAP-70 þ CD38 þ as compared to the ZAP-70 À CD38 À CLL patients. Moreover, Ang-2 plasma levels detected in Binet B and C patients exceeded those of Binet stage A cases, suggesting a correlation between Ang-2 secretion and CLL progression.…”
mentioning
confidence: 99%